COMPUTATIONAL SOCIOLOGY: APPLICATION AND DEVELOPMENT - Prasetyo, Yanu (University of Muhammadiyah Malang, 2019)
Along with the popularity of research on Big Data and the increasingly massive use of computer as well as internet-based research, the development of studies with a computational sociology approach has also received more attention. Computational sociology approach such as agent-based modeling or social network analysis has become a new landmark of the interest of social scientist around the world to continue develops suitable interdisciplinary research approaches. This article makes mapping and visualizing the trends and developments of computational sociology studies through a systematic review and bibliometric analysis of scientific publications in the Scopus database. Concepts and clusters of studies on contemporary computational sociology are discussed, including international journals that have a focus and interest in this approach and research area.